PENGEMBANGAN E-LKPD BERBASIS KOMIK DENGAN APLIKASI CANVA MATERI CAHAYA KELAS V - Rohayati; Fitri Siti Sundari; Tatang Muhajang (STKIP Subang, 2026)
Grade V students of SDIT Al-Ghozali showed low enthusiasm in learning Natural and Social Sciences (IPAS), particularly on the topic of light, due to the use of conventional worksheets that were monotonous and less engaging. This condition hindered the learning process, indicating the need for innovative, interactive learning media that align with students’ characteristics. This study aimed to develop and evaluate a comic-based electronic worksheet (E-LKPD) using the Canva application for the light topic for Grade V students in the 2024/2025 academic year. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The research subjects included media, language, and content experts as validators, as well as 24 Grade V students as trial respondents. Data were collected through questionnaires, observations, interviews, and documentation, and analyzed qualitatively and quantitatively to determine validity, effectiveness, and user responses. The results showed that the comic-based E-LKPD demonstrated a very high level of validity, with feasibility percentages of 94% from media experts, 92% from language experts, and 96% from content experts. Student responses to the use of the E-LKPD reached 94%, while teacher evaluations achieved 100%. Student learning outcomes also improved significantly, as indicated by post-test scores ranging from 71 to 100 and an average N-Gain score of 0.6, categorized as moderately effective. Therefore, the comic-based E-LKPD is considered feasible, engaging, and effective as a learning medium that supports 21st-century education.